A systematic review and network meta-analysis of first-line immune checkpoint inhibitor combination therapies in patients with advanced non-squamous non-small cell lung cancer - Shao, Taihang; Zhao, Mingye; Liang, Leyi; Tang, Wenxi (Frontiers in Immunology, 2022)
Introduction: Clinical evidences have pointed out that first-line immune checkpoint inhibitors (ICIs) combination therapies can improve survival benefits of patients with advanced non-squamous non-small-cell lung cancer (nsq-NSCLC). However, optimal strategy remains unknown without a systematic comparison on the long-term effect. Methods: We performed a systematic review and network meta-analysis through retrieving up-to-date literature from PubMed, Embase, Medline, ClinicalTrials.gov, and major international conference publications. Published studies and abstracts comparing first-line ICIs combination therapies with other treatments for patients with advanced nsq-NSCLC were included. Restricted mean survival time (RMST) was used to evaluate short-term effects, and Royston-Parmar model was used to extrapolate and compare for the long-term outcomes. This study has been registered in PROSPERO (CRD42022325005). Results: We included a total of 11 trials involving 12 therapies and 6130 patients. Pembrolizumab plus chemotherapy exhibited the best overall survival benefit in both 18 and 60 months (RMST=2.95, 95%CI: 1.96-3.97; life-years-gained over 5-year period= 26.17 months). Nivolumab plus bevacizumab plus chemotherapy was found to present the best PFS benefit in 12 months (RMST 3.02, 95%CI: 2.11-3.91) while atezolizumab plus bevacizumab plus chemotherapy showed the best PFS benefits in 36 months (life-years-gained over 3-year= 14.64 months). Subgroup analyses showed that for patients with PD-L1 expression≥ 50%, atezolizumab plus chemotherapy and nivolumab plus ipilimumab exhibited superior OS benefits in 18 months and 60 months respectively. For patients with PD-L1 expression< 1%, pembrolizumab plus chemotherapy was associated with OS benefits in both 18 months and 60 months. Sintilimab plus chemotherapy was associate with relative fewer grade≥ 3 adverse events than other ICIs combination therapies. Conclusion: Our results revealed that ICIs combination therapies showed better survival benefits than chemotherapy. Pembrolizumab plus chemotherapy could provide the best OS benefits to patients with advanced nsq-NSCLC while atezolizumab plus bevacizumab plus chemotherapy could bring best PFS benefits. The optimal ICIs combination therapies varies with different PD-L1 expression levels.